Learning Mathematics Through Mathematical Modelling Processes Within Sports Day Activity - Sakon Tangkawsakul; Nuttapat Mookda; Weerawat Thaikam (Southeast Asian Mathematics Education Journal, 2020)
Applying mathematics in real-life situations is an important objective of mathematicseducation. Yet in Thailand, the students ' ability to connect mathematics to real-life situations is insufficient. In this study, we adapted the school sports day to provide opportunities to relate real-life situations with mathematical knowledge and skills. This study aims to describe the students' responses and the teacher's interaction during a modelling task. The designing of the modelling task, inspired by the realistic Fermi problems, involves collaboration between mathematics teachers and educators and the participation of 10th grade students. The task is set in the context of bleacher in the school sports day. Each experiment's modelling task lasted for 45 minutes and was conducted in the one-day camp with 45 students. Data were collected through observation, interview, and written task before being analysed through content analysis. The results showed that the students who had no previous mathematical modelling experience engaged in mathematical modelling processes with their friends under the guidance and support of the teacher. Most of them were able to think, make assumptions, collect data, observe, make conjectures and create mathematical models to understand and solve the modelling task.